Trafficking SNARE SYP132 Partakes in Auxin-Associated Root Growth. Issue 4 (23rd January 2020) - Xia, Lingfeng; Mar Marquès-Bueno, Maria; Karnik, Rucha
Abstract : Auxin regulates abundance of the trafficking SNARE SYP132 over the time course of root growth and gravitropic responses.